PEMETAAN KASUS COVID-19 MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI PROVINSI BALI 2020 - I Gede Bagus Wangsa Ariadi; I Nyoman Mahayasa Adiputra; Viktorinus Alfred Saptiono Mulana (Jurnal Teknologi Informasi dan Komputer, 2022)
ABSTRACTBackground Covid-19 is a new virus that first appeared at the end of 2019, thecovid-19 virus is zoonotic, this virus can cause symptoms from mild to severe. TheCovid-19 virus can spread quickly if you have direct contact with a positive person.The purpose of this study was to find out how the description of the distribution ofCOVID-19 cases in Bali Province in 2020 using GIS. Subjects and Methods: Thisresearch is descriptive using in-depth library study method. The population in thisstudy was all COVID-19 data in Indonesia in 2020. The sampling technique in thisstudy used the purposive sampling method with a sample of all Covid-19 data in theProvince of Bali 2020. Results: From the results of the mapping conducted usingQGIS, it was found that the area with The highest number of COVID-19 is Badung,Denpasar, and Gianyar. The peak of cases was in December with the highestaccumulation of cases in Denpasar (4759), Badung (3139), and Gianyar (238).Conclusion: This study can be concluded that by mapping COVID-19 cases in theprovince of Bali using GIS, it can be seen about the distribution of Covid-19 cases ineach area in the Province of Bali.Keywords: GIS, Covid-19, MappingABSTRAKLatar Belakang: Covid-19 merupakan virus baru yang pertama kali muncul padaakhir 2019, virus covid-19 menular secaraa zoonosis virus ini dapat menyebabkangejala dari ringan samapi berat. Virus covid-19 dapat menyebar dengan cepat jikamelakukan kontak langsung dengan orang posiftif. Tujuan dari penelitian ini untukmengetahui bagaimana gambaran sebaran kasus covid-19 di Provinsi bali tahun2020 menggunakan SIG. Subjek dan Metode: Penelitian ini adalah deskriptifmenggunakan metode studi Pustaka mendalam. Populasi pada penelitian ini adalahseluruh data covid-19 di Indonesia tahun 2020. Hasil: Dari hasil pemetaan yangdilakukan menggunakan QGIS diperoleh daerah yang memiliki jumlah kasus covid-19 tertinggi iyalah Badung, Denpasar, dan Gianyar. Puncak kasus berada pada bulandesember dengan akumulasi kasus tertinggi berada di kabupaten Denpasar (4759),Badung (3139), dan Gianyar (238).Kesimpulan: Penelitian ini dapat disimpulkanbahwa dengan pemetaan kasus covid-19 di provinsi bali menggunakan SIG dapatdiketahui tentang sebaran kasus covid-19 pada setiap daerah di Provinsi BaliKata kunci: SIG, Covid-19, Pemetaan